Planning and Management of Recreation in Icelandic Forests: Developing infrastructure (input) strategies based on preference and benefit (output) analysis - Sherry Curl 1957- (2008)
Opportunities for forest recreation are relatively new in Iceland, as are the forests. No framework for planning and management exists for recreational forests in Iceland and data necessary for constructing such a framework are lacking. In order to provide the necessary data, a self-administered mail-in survey was designed to answer the following questions: 1) Are there distinct user groups? 2) If such groups exist, are the differences between them significant enough to form the basis of a framework? 3) What benefits (outcomes) are being sought by forest users? 4) Is the Importance-performance estimate a useful tool for monitoring the quality of recreational forests in Iceland? Survey respondents were recruited from two day-use and two overnight-use forests. ANOVAs were performed on the data using three categories: social groups, benefit groups and forest types, i.e. day-use and overnight-use. The data were also used in an Importance-performance analysis for each of the forests. Preference differences for infrastructure and management among social and benefit groups were insufficient for a planning and management framework. However, there were sufficient differences found between day-users and overnight-users to construct such a framework, with overnight-users placing a greater emphasis on security, access to water, nearness to shops and other things related to the duration of their stay. There were also clear differences in types of benefits (outputs) accruing to recreationists, with respondents in all forests mostly emphasizing restorative benefits, learning, social ties and spiritual benefits. User preferences were used to construct priority indices for use in selecting new areas for recreational development and improving existing recreational forests. The Importance-performance estimate proved to be a useful tool in gauging the quality of recreational infrastructures in the forests. It should also provide a method for evaluating the efficacy of improvement efforts and be a basis for formulating quality ...